Perceptions of nursing academics about surgical patient assistance with sepsis in the surgical clinic (Research, Society and Development, 2021)
Objective: the present study aims to describe the perceptions of nursing students about assistance to patients with sepsis in a surgical clinic. Methodology: This is an experience report, developed from the assistance to patients with sepsis during curricular practices in the supervised internship of the Nursing course at a general hospital in the state of Bahia. Data were collected from March 21 to April 28, 2019, from the situations observed during care for patients with sepsis, dialogue between professionals, patients and family members. The information was recorded in a field diary. Results and discussion: It was realized that patient care should be carried out in intensive care units, since treatment requires specialized care, with the use of technologies and continuous assessment. In municipalities or hospital units without this specialized structure, it is necessary for the local permanent education nucleus to carry out periodic training and institutionalize care protocols in order to standardize the care provided, focusing on early diagnosis. Given the complexity of care, nursing care is essential in all phases of care, from diagnosis and treatment, to communication and building bonds with family members. Conclusion: it is essential to create strategies for training the multidisciplinary team and protocols aimed at early diagnosis and treatment of patients with sepsis outside the intensive care unit.